Potencjał konkurencyjności polskich zakładów ubezpieczeń majątkowych na tle warunków konkurowania w Unii Europejskiej - Glabiszewski, Waldemar (Competitive Potential of Non-Life Insurance Companies in Poland, 2008)
The company's competitive potential taken as widely understood resources, both material and immaterial, constitutes a source of shaping its competitiveness. It determines then the company's ability to compete effectively and reach market success - realization of the set strategic goals. The article is the author's attempt to evaluate the condition of competitiveness of non-life insurance companies in Poland, especially as regards the EU requirements for the insurance market. The presented research outcome indicates that the possessed resources are not sufficient for creation of competitiveness instruments that would allow an effective competition in the non-life insurance sector in Poland.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1197, s. 80-87